DESAIN MEDIA BERBASIS ACTIVE LEARNING PADA SISWA KELAS XI DI SMA KOTA PALANGKA RAYA - Yuliani, Hadma; Annovasho, Jhelang; Hasanah, Siti Rabiatul; Ningsih, Eka Wahyu (Jurnal Pendidikan Fisika FKIP UM Metro, 2024)
This research was conducted with the aim of producing an E-module based on Active Learning on physics subjects for class XI SMA. This research was conducted in 7 high schools in Palangka Raya City with the total number of respondents being 186 students. The research method used is the development of ADDIE with the stages including Analysis, Design, Development, Implementation and Evaluation. The analysis of the data used in this study is based on the results of the recapitulation of the feasibility test scores obtained from media expert validators and material expert validators. The results of the recapitulation of the feasibility test scores obtained from media experts amounted to 92.07% with a very decent category. While the results of the recapitulation of the feasibility test scores obtained from material experts are 91.85% in the very feasible category. Based on the results of this study, it can be concluded that the Active Learning-based E-module in Physics class XI SMA is very feasible to be used as one of the learning media for students.